Innovation in proximal femoral replacement for oncology patients—A novel eggshell procedure - Jiazheng Zhao; Xiaowei Ma; Helin Feng (Journal of Bone Oncology, 2023)
Purpose: Proximal femoral replacement (PFR) for oncology patients is gaining interest as a limb salvage operation due to its obvious advantages. However, almost all hip replacement surgeries including PFR, are faced with the challenge of how to reconstruct the functional musculature in an optimal way. To address the challenge, we have developed an innovative eggshell procedure and through this study we aim to investigate the specific efficacy of the procedure. Methods: A total of 44 tumor patients with PFR surgery were incorporated into the study, including 12 who underwent the eggshell procedure and 32 who did not. General characteristics, short-term indicators, long-term indicators and complication outcomes were compared successively between the two groups of patients. Results: No significant differences were identified in general characteristics between the two groups. Overall, in terms of both short-term and long-term indicators, the patients with eggshell procedure performed significantly superior to the patients without it. Moreover, the eggshell procedure significantly reduced the incidence of associated complications, including prosthesis dislocation and hip pain. Conclusions: Our eggshell procedure is convenient and accessible. On the one hand, it can reduce surgical side injuries without adding additional complications, and on the other it allows to improve joint mobility and life quality while diminishing the incidence of prosthesis dislocation and hip pain. Despite it may still remain limitations, we have reasons to believe that this procedure can be further promoted and applied.